SYNTAX AND ITS CORE CONSTITUENTS: A COMPARATIVE ANALYSIS OF TRADITIONAL AND COGNITIVE APPROACHES TO SYNTACTIC THEORY ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the concept of syntax, its main units, and contrasts traditional and cognitive approaches to understanding sentence structure. It begins by defining syntax as the study of how words and phrases are arranged to convey meaning, emphasizing key syntactic units such as words, phrases, clauses, and sentences. Traditional approaches, particularly structuralism and generative grammar, are discussed for their focus on formal rules and innate grammar structures that govern sentence formation. In contrast, cognitive approaches, including cognitive linguistics, construction grammar, and usage- based theories, highlight how syntax is linked to human cognition and experience, emphasizing the role of perception, conceptual metaphors, and language use patterns. The article concludes by noting the importance of both traditional and cognitive perspectives, suggesting that an integrated approach could offer a more complete understanding of syntax, blending formal structures with cognitive processes.